2010
DOI: 10.1094/pdis-94-5-0596
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Rainfall and Mowing Impact Fungicide Performance When Targeting Dollar Spot in Creeping Bentgrass

Abstract: In this 2-year field study, four chemically diverse fungicides (i.e., chlorothalonil, boscalid, iprodione, and propiconazole) were evaluated for their ability to control dollar spot (Sclerotinia homoeocarpa) in creeping bentgrass (Agrostis stolonifera) as affected by simulated rain and mowing timing. Simulated rain (25 to 32 mm) was imposed about 30 min after fungicide application and was compared to rain-free plots. One set of plots was mowed in the morning when the canopy was wet with dew and compared to plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…The reduced control of early blight following application of the fungicides iprodione and boscalid after exposure to simulated rain was also noted by Pigati, Dernoeden, and Grybauskas (2010) while studying the control of Sclerotinia homeocarpa on golf courses. In experiment 2, the greater rainfastness observed for boscalid, when compared to iprodione, may be explained by its greater systemicity in relation to this dicarboximid (HEWIT, 1998;RHEINHEIMER, 2007).…”
Section: Resultsmentioning
confidence: 82%
“…The reduced control of early blight following application of the fungicides iprodione and boscalid after exposure to simulated rain was also noted by Pigati, Dernoeden, and Grybauskas (2010) while studying the control of Sclerotinia homeocarpa on golf courses. In experiment 2, the greater rainfastness observed for boscalid, when compared to iprodione, may be explained by its greater systemicity in relation to this dicarboximid (HEWIT, 1998;RHEINHEIMER, 2007).…”
Section: Resultsmentioning
confidence: 82%
“…Dollar spot was allowed to develop to trace levels [i.e., seven dollar spot infection centers/plot or less (DSIC)] in the study areas to ensure the epidemic had begun, as has been done in previous studies (McDonald et al, 2006;Pigati et al, 2010). Fungicide treatments included Daconil Ultrex 82.5 WDG Ò (chlorothalonil: 2,4,5,6-tetrachloroisophthalonitrile; Syngenta Crop Protection, Greensboro, NC) applied at 8.17 kg a.i./ha, Banner Maxx were treated with two applications of TE on a 14-d interval before fungicide application.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Delvalle et al (2011) reported that dollar spot control with fungicides can be extended by daily dew removal or increased mowing frequency. Increased mowing frequency likely results in a reduction of dollar spot as a result of dew removal as well as physical disruption and removal of inoculum (Delvalle et al, 2011;Pigati et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study examining the effects of simulated rain and mowing timing on fungicide performance showed that mowing in the morning versus afternoon mowing significantly reduced dollar spot across all fungicide treatments (10). The authors reported 54 to 65% fewer infection centers (IC) in plots mowed in the morning compared with plots mowed in the afternoon when averaged across chlorothalonil, propiconazole, boscalid, and iprodione treatments.…”
mentioning
confidence: 99%